Synthesis and Characterization of Zirconium Phosphoborate and its Conversion into Granular Shape - Sharma, Ashok (My University, 2010)
ZrPB is reported as inorganic ion exchanger, highly selective for Er3+ ions over other lanthanides. This material was selected for its granulation. The material was synthesized by the reported procedure and characterized for its ion exchange properties like ion exchange capacity, pH titrations, thermal stability and morphology using XRD and SEM techniques. Preparation of granular ion exchanger was tried by a number of methods like sol-gel method, epoxy resin as a binder using different solvents. However these attempts were not successful.Then another method of synthesis by using Nylon-66 as a binder was tried which resulted in the preparation of granular zirconium phosphoborate. The material has been characterized as a granular material by XRD and SEM technique.
M.Sc. (SCBC)
Keywords: ZIRCONIUM PHOSPHOBORATE